EDUCATION, ECOTOURISM, AND BIOCULTURAL CONSERVATION IN THE MINIATURE FORESTS OF CAPE HORN EDUCACIÓN, ECOTURISMO Y CONSERVACIÓN BIOCULTURAL EN LOS BOSQUES EN MINIATURA DEL CABO DE HORNOS - Medina, Yanet; Massardo Vega, Cristina Elvira Francisca; Rozzi Marin, Ricardo Roberto (My University, 2020)
The Omora Ethnobotanical Park develops long-term biocultural education, research, and conservation in Puerto Williams, Cape Horn Biosphere Reserve, Chile. In 2008 it was discovered that this reserve is a hotspot of diversity of non-vascular flora, however, the community was unaware of this floristic richness. The causes of this ignorance were investigated. First, we quantified the taxonomic biases that favor (i) vascular over non-vascular flora and (ii) exotic over native flora in (a) school texts and (b) the "floristic mindsets" of schoolchildren in Puerto Williams. Second, to correct these biases the Field Environmental Philosophy (FEP) methodology was used to design and implement educational-recreational activities that incorporated and valued non-vascular flora and native flora in formal and non-formal education (including ecotourism). Third, we evaluated the impact that FEP activities and concepts had to reverse the negative bias towards non-vascular flora in schoolchildren education and in everyday culture. School texts had marked taxonomic biases favoring vascular flora and biogeographic biases favoring exotic flora. In 2000, in the mindsets of schoolchildren all plants were vascular and 73.3% of them were exotic. In contrast, in their mindsets in 2009, after using FEP's methodology, the proportions of vascular and non-vascular were similar and 44.4% species were native. Therefore, to reverse both floristic biases, the FEP methodology was effective. Particularly effective were the composition of metaphors and field activities with preschoolers, schoolchildren, university students, citizens of the local community, tourist guides, Chilean Navy personnel, and tourists. It was demonstrated that using FEP's methodology, inconspicuous species can be made visible and their ecological, ethical, aesthetic and economic values can be recognized by citizens. FEP fosters biocultural transformations that generate changes in the perception and appreciation about living beings that are generally marginalized from culture and education. FEP could be adapted to appreciate and conserve myriads of tiny living beings with which we co-inhabit other regions of Chile and the planet.
Keywords: biocultural ethics; biocultural homogenization; ecotourism with a hand-lens; field environmental philosophy; taxonomic bias